Haemostatic Factors in Human Peripheral Afferent Lymph - Miller, George J.; Howarth, David J.; Attfield, Janet C.; Cooke, C. Justin; Nanjee, M. Nazeem; Olszewski, Waldemar L.; Morrissey, James H.; Miller, Norman E. (Thrombosis and Haemostasis, 2000)
Peripheral afferent lymph was obtained by cannulation of a collecting vessel in 17 healthy men (mean age 26 years). Lymph/plasma ratios of all vitamin K-dependent factors were lower than expected from molecular weight. Factor VII, factor IX and tissue factor pathway inhibitor (TFPI) lymph/plasma activity ratios were higher than antigen ratios. Activated factor VII (FVIIa) and TFPI-Xa complex concentrations were higher in lymph than plasma, and the raised FVIIa did not appear to be due to cannulation. The fibrinogen lymph/plasma activity (Clauss) ratio averaged about 20% of the antigen ratio. The result of an ELISA for D-dimer was higher in lymph than plasma, often more than five-fold. This high level in lymph was not explored but may indicate proteolysis of fibrinogen and fibrin with release of D-like and D-dimerlike fragments in interstitial fluid.
Keywords: Peripheral lymph; haemostatic factors; D-dimer